Ageing of Australian DNAN Based Melt‐Cast Insensitive Explosives. Issue 3 (24th February 2016) - Provatas, Arthur; Wall, Craig
Abstract: 2, 4‐Dinitroanisole (DNAN) is a new melt‐cast matrix ingredient that replaces traditional TNT in TNT‐based melt‐cast explosives. Aside from sensitiveness improvements, the use of DNAN allows for the continued operation of existing melt‐cast facilities (for example the Australian Munitions plants located at Mulwala and Benalla) without the need for major plant modifications. Researchers at Defence Science and Technology Group (DST Group) have developed several DNAN based formulations that have been extensively characterized. In an effort to better understand the ageing properties of these formulations, an accelerated ageing program was undertaken. Testing was conducted under two different ageing conditions; the first test condition was conducted at a constant 60 °C with ambient humidity and the second test condition was the A2 diurnal cycle (representative of hot dry climates). Analysis of the formulation density, sensitiveness, mechanical and thermal properties was made at three‐month intervals for a period of 12 months and results compared with conventional explosives similarly aged. For all DNAN‐based formulations there was negligible change in impact, friction, electrostatic discharge, and thermal testing over time. These results highlight the ability of the ARX formulations to diurnal temperature cycling and to hold favorable sensitiveness properties to various stimuli. Abstract :